2010
DOI: 10.1246/cl.2010.254
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Thin Film Surface Templates from Two Immiscible Polymers by Phase Separation and Phototethering

Abstract: Thin layer surface templates were fabricated by spin coating two immiscible polymers onto a photoreactive substrate, followed by photoirradiation and removal of the unreacted polymer with solvent. Phase-separation occurs during the spin coating process and the separated structure was tethered onto the substrate surface by photoirradiation, to yield a thin surface pattern on the substrate. The surface patterns thus obtained were robust, applicable to large areas, and could be tuned at will by designing componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Typical strategy of bottom-up approaches is the self-assembly of amphiphilic lipids 7 , surfactants 8 , block-copolymers 9 , polymer blends 10 or colloidal particles 11 into various patterns and periodicities. Among them, phase separation has drawn intensive attentions over the past two decades and shows great potential in fabrication of optical and electronic devices 12 , energy storage 13 , catalyst supports 14 , templates 15 16 , cell culture scaffolds 17 , and super hydrophobic surfaces 18 . Phase separation systems include block copolymers 19 20 , polymer blends 21 22 and breath figures (BF) 16 23 24 , and it has been reported that self-assembly of block copolymer with a suitable choice of immiscible segments and their chain lengths can achieve well-ordered nanostructures down to sub–20 nm scale on large areas 25 .…”
mentioning
confidence: 99%
“…Typical strategy of bottom-up approaches is the self-assembly of amphiphilic lipids 7 , surfactants 8 , block-copolymers 9 , polymer blends 10 or colloidal particles 11 into various patterns and periodicities. Among them, phase separation has drawn intensive attentions over the past two decades and shows great potential in fabrication of optical and electronic devices 12 , energy storage 13 , catalyst supports 14 , templates 15 16 , cell culture scaffolds 17 , and super hydrophobic surfaces 18 . Phase separation systems include block copolymers 19 20 , polymer blends 21 22 and breath figures (BF) 16 23 24 , and it has been reported that self-assembly of block copolymer with a suitable choice of immiscible segments and their chain lengths can achieve well-ordered nanostructures down to sub–20 nm scale on large areas 25 .…”
mentioning
confidence: 99%
“…Phase separation morphologies with microto-nanoscale features have a wide range of potential applications in patterning various substrates for lithographic templates, antireflective coatings, , superhydrophobic surfaces, optoelectronic devices, solar cells, and biochips. , Fabrication of nanostructures with high aspect ratios is strongly desirable for subsequent pattern transfer. The morphology and domain scale of the phase separation are highly dependent on the thickness of the spin-casted film .…”
Section: Resultsmentioning
confidence: 99%
“…However, so far there is no direct way to use the resulting polymer blend film as a lithographic mask, because the formed structure contains both lateral and layered phase separations [ 49 51 ]. Special techniques, such as UV curing have to be combined to make the film ready for lithographic applications [ 52 53 ]. Zemla et al [ 52 ] describe a technique where after cross-linking one polymer, the other one is removed, and a protein is adsorbed at the free surface areas.…”
Section: Introductionmentioning
confidence: 99%
“…The second polymer, however, cannot be dissolved due to the cross-linking and remains on the substrate. Kawamura et al [ 53 ] use the difference in resistance to photo-etching between the two polymers in the blend to remove the component with less stability under photo-irradiation. The remaining micropatterned polymer layer has a thickness of about 3 nm, albeit without a well-defined surface chemistry.…”
Section: Introductionmentioning
confidence: 99%